The Role of Electronic Evidence in Proving Crimes in the Digital Era - Edy Sugiarto (Siber International Journal of Advanced Law (SIJAL), 2025)
Current development the more rapidly which is followed with development something technology information that can help work human , become means education and become a field For get rupiah coffers . A technology is wrong One tool which can make it easier man in all activities activities and matter This No can separated One each other, and Already become something attachment between humans and technology . One of them crimes brought about by development and progress technology information is crime related to with Internet applications. Crime This in term foreign often called with “Cyber Crime Scientific Article This Use study law normative or study law literature that is research conductedwith method research material library or secondary data, and types research on writing This is study juridical normative, namely reviewed with approach legislation It means something problem will seen from aspect the law with examine regulation legislation. Research results show that the law in Indonesia is still need to be completed For form arrangement about company individual This in regulation legislation separate from the ITE Law. Important conclusions from study This is need form this Electronic Evidence arrangement in regulation legislation invitation separately outside the Criminal Procedure Code.